Mouthguard and Sports Drinks on Tooth Surface pH - Maeda, Y.; Yang, T.-C.; Miyanaga, H.; Tanaka, Y.; Ikebe, K.; Akimoto, N. (International Journal of Sports Medicine, 2014)
The influence of sports drinks and mouthguards on the pH level of tooth surface was examined. A custom-made mouthguard was fabricated for each subject. The pH level was measured by electric pH meter with sensitivity of 0.01 up to 30 min. Sports drinks (pH=3.75) containing 9.4% sugar were used in this study. Measurements were performed on a cohort of 23 female subjects without a mouthguard (control), wearing a mouthguard only (MG), wearing a mouthguard after 30 ml sports drink intake (SD+MG), wearing a mouthguard during a 5-min jogging exercise (MG+EX) and wearing a mouthguard during jogging after sports drink intake (SD+MG+EX). For 7 male subjects, the same measurements were performed while a sports drink was taken over the mouthguard (MG+SD, MD+EX+SD). MG showed statistically higher pH level than control (p<0.05). SD+MG exhibited a significant decrease in pH level, and SD+MG+EX exhibited even below the critical level of pH 5.5 in some subjects. When sports drinks were taken over the mouthguard, no significant differences in pH level were observed among the different conditions.Within the limitations of this study, it was suggested that wearing a mouthguard during exercise is in itself not a possible risk factor for dental caries, while wearing a mouthguard after consuming sports drinks is.
Keywords: mouthguard; dental caries; sports drinks; exercise